2021
DOI: 10.1021/acsomega.0c05264
|View full text |Cite
|
Sign up to set email alerts
|

Novel Fatty Acid in Cordyceps Suppresses Influenza A (H1N1) Virus-Induced Proinflammatory Response Through Regulating Innate Signaling Pathways

Abstract: Influenza virus (IV) infections usually cause acute lung injury characterized by exaggerated proinflammatory responses. The paucity of therapeutic strategies that target host immune response to attenuate lung injury poses a substantial challenge in management of IV infections. In this study, we chemically synthesized a novel fatty acid (2Z,4E)-deca-2,4-dienoic acid (DDEA) identified from Chinese Cordyceps by using UHPLC−Q-TOF−MS techniques. The DDEA did not inhibit H1N1 virus replication but attenuated proinfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
(89 reference statements)
0
10
0
Order By: Relevance
“…Moreover, DDEA significantly reduced the protein expression levels of TLR3, RIG-I, phospho-IRF3, and phospho-NF-κB p65 in infected cells. It is suggested that DDEA may regulate the immune function by regulating TLR3 and RIG-I-dependent signaling pathways (Li et al, 2021).…”
Section: (2z4e)-deca-24-dienoic Acid (Ddea)mentioning
confidence: 99%
“…Moreover, DDEA significantly reduced the protein expression levels of TLR3, RIG-I, phospho-IRF3, and phospho-NF-κB p65 in infected cells. It is suggested that DDEA may regulate the immune function by regulating TLR3 and RIG-I-dependent signaling pathways (Li et al, 2021).…”
Section: (2z4e)-deca-24-dienoic Acid (Ddea)mentioning
confidence: 99%
“…DDEA, a fatty acid in Cordyceps sinensis , can reduce the level of inflammation caused by infection with H1N1 and reduce the secretion of inflammatory factors in cells. The anti-inflammatory effect is achieved by regulating the innate immune signal pathway activated by TLR-3-, RIG-I- and type I interferon [ 27 ]. A new polysaccharide PCP-II was isolated from Poria cocos .…”
Section: Antiviral Activitymentioning
confidence: 99%
“…It was found that four species of Pleurotus ostreatus , Fomes fomentarius , Auriporia aurea , and Trametes versicolor had an inhibitory effect on the virus. The highest treatment index of T. versicolor was 324.67 [ 27 ].…”
Section: Antiviral Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Zhong et al found that the water extract of OS had significant anti-inflammatory effects against single stimulation by cigarette smoke extract (CSE), as well as infection by a compound influenza virus [ 12 ]. A UHPLC-Q-TOF-MS technique was used to extract a novel fatty acid—(2Z,4e)-deca-2,4-dienoic acid—from CSE, which attenuated the inflammatory response by reducing mRNA and protein levels in cells [ 13 ]. The same study also found that OS contains a water-insoluble polysaccharide, β-(1,3) glucan, which is not only a component of fungal cell walls, but it is also the core structure of immunologically active polysaccharides that stimulate immune receptors such as Dectin-1 to trigger innate immune responses; this suggests that there may a large number of unknown active ingredients in OS, which could play an important role in the prevention and treatment of diseases.…”
Section: Introductionmentioning
confidence: 99%